The Chinese question : ethnicity, nation, and region in and beyond the Philippines - Hau, Caroline S., 1969- (Singapore : NUS Press in association with Kyoto University Press, Japan, 2014)
As the meanings of "Chinese" and "Filipino" evolve, intractable contradictions are appearing in the concepts of citizenship and national belonging. Through an examination of cinematic and literary works, The Chinese Question shows how race, class, ideology, nationality, territory, sovereignty, and mobility are shaping the discourses of national integration, regional identification, and global cosmopolitanism.
Citizen -- Chinese Filipino -- Capital -- Revolutionary -- Region -- Family -- "(Anglo- )Chinese."
Includes bibliographical references (pages 321-358) and index.
In English.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Chinese -- Philippines -- Ethnic identity; Chinese -- Philippines -- Social life and customs; Chinese in motion pictures; Philippines -- In literature; Philippine literature -- History and criticism; Philippines -- In motion pictures; Chinois -- Identité ethnique -- Philippines; Chinois -- Philippines -- Mœurs et coutumes; Chinois au cinéma.; Littérature philippine -- Histoire et critique; SOCIAL SCIENCE / Ethnic Studies / General; Chinese -- Ethnic identity; Chinese in motion pictures; Chinese -- Social life and customs; Literature; Motion pictures; Philippine literature; Philippines; Chinesen; Nationale Minderheit; Philippinen; Chinesen; Einwanderer; Ethnizität; Nation; Region; Philippinen; Criticism, interpretation, etc